Children's Empathy Attitude in The Storybook “Kue Kimu” By Lia Herliana And Ratu Wulan - Saidah, Kuni (Lembaga Kajian Nusantara Raya UIN Prof. K.H. Saifuddin Zuhri Purwokerto, 2024)
One of the emotional intelligences of a person is empathy, which is the ability to understand the suffering of others and to understand the opinions and feelings of others. Setting a good example and showing tolerance are important components of parenting strategies that aim to help children develop empathy. Parents should show empathy so that their children can learn from their example. Reading children's storybooks is one way to instill empathy in children, a trait that needs to be cultivated from an early age. This is because reading storybooks can stimulate children's many senses and help them become more socially intelligent. The type of research used in this study is library research. In this study, researchers used a qualitative approach which is a non-numerical data-based approach or using manuscript documents with existing thoughts. After the researchers analyzed the storybook